PTH-119 How acceptable is a 'treat to target' (T2T) approach to IBD patients in clinical remission?. (June 2019) - Carbonell, Jenelyn; Kane, John; Mandour, Omer; O'Chieng, Alvin Odouri; Pinder, Matt; McKay, Rebecca; Hamlin, John; Selinger, Christian
Abstract : Background: Treatment algorithms for IBD are shifting from traditional symptom based pathways to a 'treat to target' T2T approach aiming for clinical remission and absence of mucosal inflammation. We aimed to establish whether patients with IBD in clinical remission agree to this more intense approach. Methods: We recruited patients in steroid-free clinical remission from IBD clinics. CRP, faecal calprotectin, Hospital Anxiety and Depression Score (HADS), medication adherence and short knowledge questionnaire were recorded. Patients underwent a face to face structured interview asking them to imagine that a test had shown active inflammation and to rate how acceptable a T2T approach is to them on 10 point Likert scales. Patients rated the avoidance of complications according to level of risk and potential risk reduction. We analysed factors associated with agreement to T2T. Results: The cohort comprised 298 patients (144 CD, 136 UC, 18 IBD-U, median age 46 years, 145 males, median disease duration 7 years). Medications included Mesalazine 44.3%, Thiopurines 30.5%, Methotrexate 3.2% and Biologics (26.1%). Abnormal HADS scores were present in 28.9% (anxiety) and 18.5% (depression). Non-adherence occurred in 15.8%. Median knowledge score was 3 out of 10. Elevated CRP was found in 24.4% and elevated calprotectin in 17.7%. Patient reported current control of IBD correlated with calprotectin (pearson -0.169; p=0.004). Patients rated a T2T approach as acceptable (Likert scale ≥8) in 66.2%. Acceptable treatment aims for patients were avoidance of a flare (risk needed to be ≥30% and relative risk reduction 25%), hospitalisation, surgery and colorectal cancer (risk ≥10%, risk reduction 50% for all). Age, diagnosis, phenotype, surgical history, disease duration, patient knowledge, adherence, anxiety, depression, medication adherence and patient reported control of disease were not associated with accepting a T2T approach. Patients on 2nd line anti-TNF were more likely to agree to a T2T approach (p=0.012) but there were no associations with other treatments. Conclusion: It is important to understand patient views on T2T before attempting implementation. We have demonstrated, in a cohort of patients in clinical remission where this question is most pertinent, that 66% accept a T2T approach. Patients having experienced previous loss of response to an anti-TNF were more likely to accept T2T but at the same time are the least likely to benefit. Conversely a third of patients did not agree with this approach, and the presence of occult mucosal inflammation was not associated with T2T acceptance. Patient education and counselling materials will therefore need to be developed to convince patients of the importance of T2T.